Romantic Geography : In Search of the Sublime Landscape - Tuan, Yi-fu, 1930- (Book collections on Project MUSE., 2013)
Geography is useful, indeed necessary, to survival. Everyone must know where to find food, water, and a place of rest, and, in the modern world, all must make an effort to make the Earth -- our home -- habitable. But much present-day geography lacks drama, with its maps and statistics, descriptions and analysis, but no acts of chivalry, no sense of quest. Not long ago, however, geography was romantic. Heroic explorers ventured to forbidding environments -- oceans, mountains, forests, caves, deserts, polar ice caps -- to test their power of endurance for reasons they couldn't fully articulate. Why climb Everest? "Because it is there." In this book, the author considers the human tendency -- stronger in some cultures than in others -- to veer away from the middle ground of common sense to embrace the polarized values of light and darkness, high and low, chaos and form, mind and body. In so doing, venturesome humans can find salvation in geographies that cater not so much to survival needs (or even to good, comfortable living) as to the passionate and romantic aspirations of their nature